Distributed task offloading in a multi-tier cloud infrastructure - Pandey, Pratyush Kumar (Nanyang Technological University, 2023)
With the advent of edge computing, computational servers were brought closer to end devices to reduce the latency of offloading tasks. This has led to a sharp rise in the number of mobile-edge applications. Due to the heterogeneous requirements of such applications, efficient resource management in an edge infrastructure is a challenging problem. In this study, we propose a distributed task offloading algorithm for a multitier cloud infrastructure. The algorithm involves a search routine that uses Ant Colony Optimization (ACO) to search for the optimal solution, and a consensus routine for all the hosts to converge on the best solution. An asynchronous distributed environment was to evaluate and compare its performance with its centralized counterpart. Results show the effectiveness of the distributed algorithm in reducing the computational complexity without compromising on the optimality of the solution. The proposed algorithm could help scale the modern cloud/edge infrastructure to cater to the rising number of services.